Photographs in Instagram: images of corporate practices and sociabilities in public parks leisure citadines - Augusto Cesar Rios Leiro; Ednaldo da Silva Pereira Filho; Paulo Cesar de Carvalho Lima (Universidade Federal de Santa Catarina, 2019)
The objective of this article is to identify and reflect on human sociabilities by analyzing images - photographed and transmitted in the Instagram - of corporal practices in public urban leisure parks. It is an exploratory study of quantitative-qualitative nature of images captured in Instagram and taken here as a frame, through the system of search and tracking of the geolocation of two public parks of Brazilian metropolitan cities and that were imported to MAXQDA in order to facilitate the categorization and elucidation of qualitative information. As a first synthesis, sociabilities express themselves singularly on the internet alongside spectacular images of daily life of subjects, who at the instant they make their posts are producing social relations mediated by images, thus narrowing their social circles. In this way, real space and virtual space do not constitute distinct environments when it comes to human sociability.